Effects of ullage height on heat feedback and combustion emission mechanisms of heptane pool fires. (September 2021) - Liu, Chunxiang; Ding, Long; Jangi, Mehdi; Ji, Jie; Yu, Longxing
Abstract: This paper investigates the effects of ullage height (distance between the fuel surface and the pool upper rim) on heat feedback and combustion emission mechanisms of heptane pool fires. Results showed that ullage height significantly influences the flame structure and fuel mass loss rate. The incident radiative heat flux to the fuel surface and its heat feedback fraction first increase and then decrease with ullage height. Correspondingly, the convective heat feedback fraction presents a reverse trend. This attributes to flame base suspension effect and the evolution of soot volume fraction of the flame due to incomplete combustion. While for the conductive heat feedback fraction, it increases with ullage height and becomes the dominant heat feedback mode when the ullage height increases to a certain value. The profiles of the generation rate of the smoke particulates well explain the evolutions of the incident radiative heat flux. The combustion completeness is characterized by the ratio of CO/CO2 . Furthermore, it is calculated that the maximum combustion completeness decreases by 18.4% and 14.3% for pool diameters of 10 cm and 15 cm, respectively. These findings will help to develop and establish more general heat transfer and heat release rate models for pool fires.